Localising an online computer software to include Setswana, an indigenous African language, for the South African teacher - Moodley, Meganathan (My University, 2021)
The introduction of information and communication technology (ICT) into the South African education sector has brought optimism that ICT can enhance education, and at the same time trepidation whether it will benefit all South Africans. Research, in general, has shown that acceptance of ICT in education is low because of limited access and low ICT skills. However, emerging research shows that the acceptance of ICT is influenced by context, culture, and language. There exists an erroneous belief that ICT is more suited for the richer countries and communities, which has resulted in the need to rethink the traditional conceptualisation and design of ICT resources. Evidence shows that South African English speakers are no longer the main users of ICT and that there is steady growth among Indigenous African language speakers. Hence, it is important to accommodate the country’s diverse linguistic groups in ICT. The continued dominance of English in ICT will only serve to alienate potential users. This study aimed to examiner how the introduction of educational software with a dual English-Setswana interface and content can influence teachers’ user experience of the software and their attitude towards the use of African languages in ICT. The conceptual framework adopted in this study merged the Technology Acceptance Model and the theory of colonial mentality to explain the findings. The study’s population was teachers from the North West province who were introduced to the dual-language software. Data was collected using systematic self-observation, participant observation and interviews. Trustworthiness of the study was achieved using several data collectors and external data transcribers. To maintain a high level of ethical compliance, names of participants and schools were excluded from the research report. The findings indicated that while the teachers felt pride and easiness using the Setswana software and were happy with the translation, they were concerned about the non-translated terms and the neglect of dialect accommodation. Even though the teachers completed the tasks on the Setswana version with ease, they acknowledged that English was better suited for use in ICT. The conceptual framework adopted in this study merged the Technology Acceptance Model and the theory of colonial mentality to explain the findings. Based on these findings, it is recommended that consultations with relevant language and cultural experts and the target end-users are necessary for software localisation. Furthermore, more research is needed on the role of colonial mentality in the acceptance of technology by Indigenous populations
A thesis submitted to the Faculty of Education, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree Doctorate in Education, 2020
Keywords: Computational linguistics-South Africa; African languages